AI Usage and Job Transformation in Malaysia: Examining Workforce Awareness and Behavioural Change - Muriatul Khusmah, Musa; Murshamshul Kamariah, Musa; Siti Haslina, Hussin; Mohamad Zain, Hashim (Asian Scholars netwrok, 2025)
The emergence of Artificial Intelligence (AI) technology has brought significant transformation to the modern work environment, particularly in aspects of productivity, task automation, and decision-making effectiveness. However, the success of AI implementation in the workplace greatly depends on employees’ level of awareness and their readiness to adapt their behaviour toward the technology. This study was conducted to assess employees’ awareness of AI usage and to analyse the relationship between such awareness and changes in work behaviour among employees across various sectors in Malaysia. A quantitative approach was employed using a questionnaire as the main instrument, consisting of four sections: demographics, awareness of AI, behavioural changes, and open-ended questions. A total of 38 respondents were selected through stratified random sampling. Data were analysed using SPSS software through descriptive statistics, reliability analysis, and Pearson correlation. The findings revealed that respondents demonstrated a high level of awareness of AI (overall mean = 4.13), although only a small proportion had received formal AI-related training. The behavioural change results indicated a moderate inclination toward positive outcomes, particularly in terms of increased confidence and improved work efficiency. Pearson’s correlation analysis showed a moderate and statistically significant relationship between awareness and behavioural change (r = .491, p = .002). These results align with the Technology Acceptance Model (TAM), underscoring the critical role of AI literacy as a foundation for technology adoption and organizational transformation. The implications suggest that organizations should implement structured training programs and cultivate a workplace culture that promotes the responsible use of AI. The study further recommends targeted interventions focusing on awareness-building, AI ethics, and institutional support to empower employees in navigating the digital transformation era. Keywords: Artificial Intelligence, AI awareness, Behavioural change, workplace, Technological literacy